Examining the interplay of coaches leadership styles and mental toughness in university student-athletes / Nur Athirah Mat Hisa and Mohamad Firdaus Ahmad - Mat Hisa, Nur Athirah; Ahmad, Mohamad Firdaus (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the relationship between coaches’ leadership styles and mental toughness among student-athletes at UiTM Seremban during KARiSMA Negeri Sembilan 2024. It aims to identify preferred leadership styles[1] , key mental toughness factors, and their interrelationship. Addressing a research gap in understanding how leadership influences mental toughness, the findings will provide insights to enhance coaching strategies and athlete development at UiTM and similar institutions. This quantitative study employed a non-experimental survey design with simple random sampling to gather data from 112 UiTM Seremban student-athletes participating in KARiSMA Negeri Sembilan 2024. The Leadership Scale for Sport (LSS)[2] assessed coaches' leadership styles, while the Mental Toughness Questionnaire-48 (MTQ48)[3] evaluated mental toughness. Questionnaires included demographic, leadership style, and mental toughness sections, with 5-point and 4-point Likert scales for responses.